Deltoid muscle characteristics in wrestlers - Mandroukas, A.; Heller, J.; Metaxas, T. I.; Christoulas, K.; Vamvakoudis, E.; Stefanidis, P.; Papavasileiou, A.; Kotoglou, K.; Balasas, D.; Ekblom, B.; Mandroukas, K. (International Journal of Sports Medicine, 2010)
The purpose of the present study was to investigate the deltoid muscle characteristics of wrestlers. Nine Greco-Roman competitive male wrestlers (mean age 20.1±2.7 yrs, height 175±0.6 cm, weight 83.2±12.5 kg, years of training 7.6±2.7 yrs) participated in this study. Six male healthy sedentary students (mean age 21.2±0.9 yrs, height 180±0.3 cm, weight 80.1±9.4 kg) served as controls. Muscle fibre distribution, cross-sectional area (CSA), as well as satellite cells, myonuclei and capillary density per muscle fibre area were determined by immunohistochemistry. Myosin heavy chain MHC isoform composition of single fibres was determined with protein electrophoresis. Immunohistochemical analysis showed that muscle fibre distribution of the MHC I and IIA were significantly higher in wrestlers than in controls (p<0.05). Electrophoretic analysis of single fibres revealed a significantly higher proportion of fibres containing MHC I and IIC in wrestlers (p<0.05). The mean CSA of type IIA fibres and the number of myonuclei per type II was significantly higher in wrestlers (p<0.05). We also found that the number of satellite cells was 2.5 fold higher in wrestlers than in the control group. This study suggests that the observed muscle fibre profile in the deltoid of wrestlers may represent an adaptation based on the specific mechanical and biochemical demands of the long-term training in Greco-Roman wrestling.